Effect of diet on productivity and body composition of Moina macrocopa (Straus, 1820) (Branchiopoda, Cladocera, Anomopoda) - Suhaimi, Hidayu; Yuslan, Amirah; Mhd Ikhwanuddin; Md. Yusoff, Fatimah; Mazlan, A. G.; Habib, Ahasan; Mustafa Kamal, A. H.; W. Rasdi, Nadiah (Brill Academic Publishers, 2022)
In the aquaculture of fish and crustaceans, the indoor culture of M. macrocopa constitutes a requisite to produce a more effective feed for the larviculture of the cultured commercial species. The present study examined the efficiency of different diets on population density, survival, and productivity of M. macrocopa. The cladocerans [Cladocera: currently largely referred to as Diplostraca] were fed and enriched with seven diets, including Chlorella sp., agro-industrial residues (rice bran and soybean meal), bio-organic fertilizer (chicken manure and swiftlet waste), canola oil and artificial micro pellets. The diets were provided at a concentration of 500 mg/l for each diet. The M. macrocopa fed on rice bran had a higher population density, survival, productivity, and a promising higher nutrient quality than the test groups fed on the other dietary treatments used. This study has covered the most important aspects of nutritional requirements to produce live feed organisms, which would provide a comprehensive data set for an alternative solution of the best feed for M. macrocopa propagation and their utilization in hatcheries.